GE_GERICHTE P/21184/2018 vom 20. Januar 2020 - GE Cour de justice (2020)
Maxime d'accusation;Violation simple des règles de la circulation routière | CPP.9; CPP.325; LCR cum.90.al1; LCR.26.al1; LCR.34.al1